(untitled) (Al-Academy, 2023)
The communication inspiration formed an essential foundations for contribute the influence individuals and recipients, whether negatively or positively, through the messages that were published and presented in them with multiple themes and viewpoints that covered all parts of the world and all age groups; it is directed to children addressing the various stages of childhood, as it simulates many goals, including what is directed through the digital use of educational data in television production, as it is considered an intellectual and mental bag to deliver ideas and expressive and aesthetic connotations to children, where the songs and cartoons carrying data on education; within adjacent relations and in a mutual direction, both of them support each other to achieve meaning and awareness. So that, the foregoing, the researcher has taken to delving into the folds of this title and its axes in a group of horizons and depth in its contents in terms of content and form; also, the exposure to the system of educational values in education and the age groups of children, as well as a review of the digital use of educational data in children’s television programs and the method of technical treatment of them; the research aims to study the subject in its aspects, and from this point of view, the researcher formulated the research problem to launch his study with the following question; what are the technical and digital uses and treatments of education data in television production, and since it aims to reveal the employment of digital employment of educational data in children’s television programmes, the approach was adopted for descriptive (content analysis) being more appropriate to achieve the goals and reach the desired results, among which lies the plurality of contents and educational values in the children’s television program from the production of data that contribute to the establishment of education through digital software to produce an expressive, semantic and aesthetic level.